The majlis campaign of Muslims in the Volga-Ural region at the beginning of the Revolution of 1905–1907 - I.K. Zagidullin (Ученые записки Казанского университета: Серия Гуманитарные науки)
A social activity form of Muslims – majlises, i.e., meetings of local residents held in private houses, public catering places, hotels, where the discussion of pressing local or social issues took place – in the Volga-Ural region at the beginning of the Revolution of 1905–1907 was analyzed in this paper. The main external factors that caused this mass phenomenon were singled out. The similarities and differences between majlises and “banquets” organized by Russian liberals during the same period were distinguished. Based on the texts of the contemporaries, the transformation of traditional banquets organized by both the urban and rural Muslim clergy into the local public centers of ethno-religious and political mobilization of the local population was reconstructed. The agenda of the discussed problems and their dynamics under the influence of new social and political events in the country were considered. It was concluded that the revolutionary situation of that time forced the majlises to become the meeting places for people representing various social classes, where they discussed the social problems and prospects of state reconstruction. They were a platform for the traditionalists and Jadids, where they argued about the urgent needs of the Muslim community and, on the other hand, served as a place for debate between the adherents of different political movements.